Decision Trees with Short Explainable Rules - Souza, Victor Feitosa; Cicalese, F.; Laber, E.; Molinaro, Marco (NeurIPS, 2022)
Decision trees are widely used in many settings where interpretable models are preferred or required. As conﬁrmed by recent empirical studies, the interpretability/explainability of a decision tree critically depends on some of its structural parameters, like size and the average/maximum depth of its leaves. There is indeed a vast literature on the design and analysis of decision tree algorithms that aim at optimizing these parameters. This paper contributes to this important line of research: we propose as a novel criterion of measuring the interpretability of a decision tree, the sparsity of the set of attributes that are (on average) required to explain the classiﬁcation of the examples. We give a tight characterization of the best possible guarantees achievable by a decision tree built to optimize both our new measure (which we call the explanation size) and the more classical measures of worst-case and average depth. In particular, we give an algorithm that guarantees O (ln n ) -approximation (hence optimal if P (cid:54) = NP ) for the minimization of both the average/worst-case explanation size and the average/worst-case depth. In addition to our theoretical contributions, experiments with 20 real datasets show that our algorithm has accuracy competitive with CART while producing trees that allow for much simpler explanations.